Polyglycolic acid fiber and its manufacturing method

By controlling melting temperature and spinning speed, polyglycolic acid fibers with targeted crystallinity, birefringence, and amorphous orientation are produced, addressing high heat shrinkage and enhancing hydrolyzability for diverse applications.

JP7602225B2Active Publication Date: 2024-12-18KUREHA CORPORATION +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020179119
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-26
Publication Date
2024-12-18
Estimated Expiration
2040-10-26

AI Technical Summary

Technical Problem

Conventional polyglycolic acid fibers exhibit high heat shrinkage rates and require improvements in hydrolyzability for various applications, including industrial and medical uses.

Method used

The production method involves setting specific conditions for melting temperature (250-300°C) and spinning speed (≥3000 m/min) to achieve polyglycolic acid fibers with crystallinity ≥20%, birefringence ≥35×10^-3, and amorphous orientation coefficient ≤0.30, which are critical for low heat shrinkability and high hydrolyzability.

Benefits of technology

The resulting fibers demonstrate low heat shrinkability and enhanced hydrolyzability, making them suitable for industrial and medical applications such as sutures and textile products, with improved thermal stability and biodegradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602225000006
    Figure 0007602225000006
  • Figure 0007602225000007
    Figure 0007602225000007
  • Figure 0007602225000001
    Figure 0007602225000001
Patent Text Reader

Abstract

To provide a polyglycolic acid fiber having a low heat shrinkage and easy hydrolysis.SOLUTION: There is provided a polyglycolic acid fiber having the following three characteristics: (A) a crystallinity is 20% or more; (B) a birefringence is 35×10-3 or more; and (C) an amorphous orientation coefficient is 0.30 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polyglycolic acid fibers and a method for producing the same. [Background technology]

[0002] Polyglycolic acid, a biodegradable aliphatic polyester, is known to have excellent mechanical properties and gas barrier properties. In addition, polyglycolic acid is used as a biocompatible material in medical materials such as bioabsorbable sutures. In recent years, the uses of polyglycolic acid have expanded, and for example, polyglycolic acid is used in materials used in oil and gas drilling operations, taking advantage of its high mechanical properties and hydrolysis properties.

[0003] Regarding methods for producing polyglycolic acid fibers, a direct spinning and drawing method, in which a spinning step and a drawing step are carried out as a continuous process, is generally considered to be a spinning method suitable for producing polyglycolic acid fibers (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2010 / 143526 Summary of the Invention [Problem to be solved by the invention]

[0005] Usually, industrial materials such as fibers are required to have a low heat shrinkage. However, the polyglycolic acid fibers produced by the above-mentioned conventional techniques have a high heat shrinkage. In addition, one of the characteristics of polyglycolic acid fibers is known to have hydrolysis properties, and further, hydrolysis properties such as ease of hydrolysis may be required depending on the application.

[0006] An object of one aspect of the present invention is to provide a polyglycolic acid fiber having low heat shrinkage and easy hydrolysis. [Means for solving the problem]

[0007] In order to solve the above problems, a polyglycolic acid fiber according to one aspect of the present invention has the following characteristics: (A) a crystallinity of 20% or more; (B) a birefringence of 35×10 -3 and (C) the amorphous orientation coefficient is 0.30 or less.

[0008] In order to solve the above problems, a method for producing polyglycolic acid fiber according to one embodiment of the present invention includes a step of discharging polyglycolic acid molten at a melting temperature T°C in an extruder from a spinneret, and a step of recovering the fibrous molten polyglycolic acid discharged from the spinneret into a gas phase at a spinning speed Vm / min to obtain polyglycolic acid fiber, and satisfies the following conditions (i) to (iii): (i) 250≦T≦300, (ii) V≧3000, and (iii) V / T≧11.5. Effect of the Invention

[0009] According to one aspect of the present invention, a polyglycolic acid fiber having low heat shrinkage and easy hydrolysis can be realized. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of an example of the configuration of a high-speed melt spinning device capable of producing polyglycolic acid fibers according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of an example of the configuration of a direct spinning drawing apparatus used in the production of a polyglycolic acid fiber of a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Polyglycolic acid fiber] 〔composition〕 The polyglycolic acid fiber according to one embodiment of the present invention has the following properties: (A) The crystallinity is 20% or more. (B) Birefringence is 35 × 10 -3 That's all. (C) The amorphous orientation coefficient is 0.30 or less.

[0012] In this embodiment, "polyglycolic acid fiber" refers to a fiber in which polyglycolic acid is the main component in the composition constituting the fiber. "Mainly composed of polyglycolic acid" means that polyglycolic acid is the most abundant component among the resin components. The content of polyglycolic acid in the composition may be 80% by mass or more, 90% by mass or more, or 100% by mass.

[0013] The polyglycolic acid may be a homopolymer or a copolymer. The other monomer from which the other structural units in the copolymer are derived may be any compound that can be polymerized with glycolic acid, and examples thereof include lactic acid, caprolactone, and trimethylene carbonate. The type and amount of the other monomer may be appropriately determined within a range in which the effects of this embodiment can be obtained.

[0014] The polyglycolic acid fiber may have other configurations as long as the effects of the present embodiment can be obtained. Such other configurations may be one or more. Examples of other configurations include a coating layer that covers the surface of the polyglycolic acid fiber.

[0015] In addition, the polyglycolic acid fiber may further contain other components within the range where the effect of this embodiment can be obtained. Such other components may be one or more, and examples thereof include additives and other thermoplastic resins. Examples of additives include heat stabilizers, end-capping agents, plasticizers, heat ray absorbers, and fillers. Examples of other thermoplastic resins include poly-L-lactic acid, poly-DL-lactic acid, poly(L-lactic acid-co-ε-caprolactone), polyhydroxybutyrate, polybutylene succinate, poly(R-3-hydroxybutyrate-co-R-3-hydroxyhexanoate), polycaprolactone, and polyvinyl alcohol. The polyglycolic acid fiber may contain a thermoplastic resin in addition to polyglycolic acid, but it is preferable that the fiber is substantially composed of a homopolymer of polyglycolic acid.

[0016] [Physical Properties] (Crystallization degree) The crystallinity of the polyglycolic acid fiber in this embodiment is 20% or more. When the crystallinity of the polyglycolic acid fiber is 20% or more, the heat shrinkage of the polyglycolic acid fiber tends to be sufficiently low. When the crystallinity of the polyglycolic acid fiber is too low, the heat shrinkage of the polyglycolic acid fiber may be high. When the crystallinity of the polyglycolic acid fiber is too high, the hydrolysis rate may be reduced.

[0017] The crystallinity of the polyglycolic acid fiber is preferably 25% or more, more preferably 30% or more, from the viewpoint of reducing the heat shrinkage rate of the polyglycolic acid fiber, and is preferably 50% or less, more preferably 45% or less, and even more preferably 40% or less, from the viewpoint of increasing the hydrolysis rate of the polyglycolic acid fiber.

[0018] The crystallinity of polyglycolic acid fibers can be determined by a density gradient tube method. The crystallinity can be adjusted by changing the V / T in the production method described below, and tends to increase as the V / T increases.

[0019] [Birefringence] The birefringence of the polyglycolic acid fiber in this embodiment is 35×10 -3 The birefringence of polyglycolic acid fiber is 35×10 -3 The above is preferable from the viewpoint of sufficiently lowering the heat shrinkage rate by forming a stable fiber structure with a high degree of orientation of polyglycolic acid. If the birefringence of the polyglycolic acid fiber is too low, the polyglycolic acid fiber becomes an oriented amorphous fiber and the heat shrinkage rate becomes high. If the birefringence of the polyglycolic acid fiber is too high, the molecular orientation may be too high, and the hydrolysis rate of the polyglycolic acid fiber may decrease.

[0020] The birefringence of the polyglycolic acid fiber is set to 40×10 in order to sufficiently reduce the thermal shrinkage of the polyglycolic acid fiber. -3 It is preferable that the value is 50×10 or more. -3 From the viewpoint of enhancing the hydrolysis property of the polyglycolic acid fiber, the birefringence of the polyglycolic acid fiber is preferably 80×10 or more. -3 It is preferable that the value is less than 70×10 -3 More preferably, it is 60×10 -3 It is even more preferable that:

[0021] The birefringence of the polyglycolic acid fiber can be measured using a polarizing microscope, and can be adjusted by adjusting the V / T in the production method described below.

[0022] [Amorphous orientation coefficient] In this embodiment, the amorphous orientation coefficient of the polyglycolic acid fiber is 0.30 or less. When the amorphous orientation coefficient of the polyglycolic acid fiber is 0.30 or less, the hydrolysis rate can be sufficiently increased. When the amorphous orientation coefficient of the polyglycolic acid fiber is too large, the hydrolysis rate may decrease.

[0023] From the viewpoint of enhancing hydrolysis resistance, the amorphous orientation coefficient of the polyglycolic acid fiber is preferably 0.25 or less, and more preferably 0.20 or less. Although the amorphous orientation coefficient of the polyglycolic acid fiber may be low, from the viewpoint of exhibiting sufficient hydrolysis resistance, it is sufficient that the amorphous orientation coefficient is, for example, 0.05 or more.

[0024] The amorphous orientation coefficient of polyglycolic acid fiber can be calculated by assuming a two-phase model of crystal and amorphous, using the crystal orientation coefficient, birefringence, and crystallinity described below. The amorphous orientation coefficient can be adjusted by the V / T in the production method described below.

[0025] [Heat shrinkage rate] The polyglycolic acid fiber of this embodiment has a sufficiently low heat shrinkage. The heat shrinkage rate of the polyglycolic acid fiber of this embodiment can be appropriately determined depending on the application of the polyglycolic acid fiber. From the viewpoint of thermal dimensional stability usually required for a fiber material, the heat shrinkage rate of the polyglycolic acid fiber at 100°C is preferably 5% or less, more preferably 2.5% or less. If the heat shrinkage rate of the polyglycolic acid fiber exceeds 5%, it may not be suitable for use as an industrial fiber and may have an adverse effect on the processing of the base fabric.

[0026] The heat shrinkage rate of polyglycolic acid fiber at 100° C. can be calculated from the length of the fiber before and after a specific heat treatment in an environment of 100° C. The heat shrinkage rate can be adjusted by the V / T in the production method described below, and tends to decrease as the V / T increases.

[0027] [Hydrolyzability] The polyglycolic acid fiber of this embodiment has a sufficiently high hydrolyzability. The hydrolyzability of the polyglycolic acid fiber of this embodiment can be appropriately determined depending on the application of the polyglycolic acid fiber. In addition, the hydrolyzability can be appropriately specified depending on the application. For example, if the polyglycolic acid fiber is used as an in vivo material, it can be determined by the molecular weight retention of the polyglycolic acid fiber after immersion in a phosphate buffer solution at 37°C for two weeks. It can be said that the lower the molecular weight retention, the higher the hydrolyzability. The molecular weight retention of the polyglycolic acid fiber of this embodiment is preferably 50% or less, more preferably 40% or less, and even more preferably 30% or less, from the viewpoint of suppressing the occurrence of inflammation when used as an in vivo material.

[0028] The molecular weight retention can be determined by the ratio of the weight average molecular weight of the polyglycolic acid fiber before and after immersion in the above-mentioned phosphate buffer solution, and the weight average molecular weight can be measured by a known method such as gel permeation chromatography. The molecular weight retention can be adjusted by the V / T in the production method described below.

[0029] [Melting point] The polyglycolic acid fiber of the present embodiment may have two or more melting peaks at a temperature of 220°C or higher as detected by differential scanning calorimetry (DSC). The two or more melting peaks are preferably at a melting point specific to the polyglycolic acid constituting the fiber and at a temperature higher than the melting point. Polyglycolic acid fibers having two or more melting peaks tend to have lower heat shrinkage. For this reason, from the viewpoint of lowering the heat shrinkage rate, it is preferable that the polyglycolic acid fiber has two or more of the above melting peaks. The number of the above melting peaks tends to be two or more as a more developed crystal structure is formed, for example, as the degree of crystallization is higher.

[0030] [Fiber diameter] The fiber diameter of the polyglycolic acid fiber in this embodiment can be appropriately determined from the range in which the effects of this embodiment can be obtained from the viewpoint of realizing the productivity and normal appearance of the polyglycolic acid fiber. If the fiber diameter of the polyglycolic acid fiber is too small, the productivity may decrease, and if the fiber diameter of the polyglycolic acid fiber is too large, it may have a negative effect on the appearance of the polyglycolic acid fiber, such as curling. From the viewpoint of suppressing a decrease in productivity, the fiber diameter of the polyglycolic acid fiber is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 12 μm or more. Moreover, from the viewpoint of suppressing a negative effect on the appearance of the polyglycolic acid fiber, the fiber diameter of the polyglycolic acid fiber is preferably 40 μm or less, more preferably 37 μm or less.

[0031] [Crystal orientation coefficient] The polyglycolic acid fiber of the present embodiment preferably has a high crystal orientation coefficient from the viewpoint of realizing low heat shrinkage. The crystal orientation coefficient of polyglycolic acid is preferably 0.85 or more, more preferably 0.90 or more, and even more preferably 0.92 or more, from the viewpoint of low heat shrinkage.

[0032] The crystal orientation coefficient of polyglycolic acid fiber can be calculated by the Wilchinsky calculation method using a diffraction intensity curve obtained from an X-ray diffraction image obtained using an X-ray diffractometer. The crystal orientation coefficient can be adjusted by adjusting the V / T ratio in the production method described below.

[0033] [Application] The polyglycolic acid fiber of this embodiment can be suitably used in applications requiring low heat shrinkage and high hydrolysis resistance, and can be used for biomedical materials such as sutures, artificial blood vessels, and cell culture substrates, fabric products such as nonwoven fabrics and clothing, and various industrial materials.

[0034] In addition, since the polyglycolic acid fiber of the present embodiment has low heat shrinkage, it is expected to have excellent dyeability. Therefore, in applications where it is applied to a living body, it is expected to be more convenient in the application by coloring it in a color that is easily visible. Furthermore, since it is hydrolyzable, it is expected to be used as a new cloth material and a material for the same, for example, by weaving the polyglycolic acid fiber of the present embodiment into a cloth and hydrolyzing it, a cloth with a distinctive texture is created.

[0035] [Action and Effect] The degree of crystallinity of the polyglycolic acid fiber of this embodiment is high, at 20% or more. The high degree of crystallinity means that the amount of crystals of polyglycolic acid in the fiber is large. In addition, the birefringence of the polyglycolic acid fiber of this embodiment is 35×10 -3 The birefringence is high, at 0.30 or less. A high birefringence means that the molecular orientation of polyglycolic acid in the fiber is high. Furthermore, the amorphous orientation coefficient of the polyglycolic acid fiber of this embodiment is low, at 0.30 or less. The amorphous orientation coefficient indicates the orientation of the amorphous phase, and a low amorphous orientation coefficient means that the orientation of the amorphous phase of polyglycolic acid in the fiber is low (disordered).

[0036] The polyglycolic acid fiber of the present embodiment has a high degree of crystallinity and a low amorphous orientation coefficient, that is, the polyglycolic acid fiber of the present embodiment has a high birefringence and therefore a high molecular orientation and a structure in which the crystalline phase is mainly developed.

[0037] Generally, an increase in distortion due to the spinning speed appears as an increase in heat shrinkage as a thermal relaxation phenomenon, but it is believed that a further increase in the spinning speed forms a stable structure having a developed crystal structure and a low-oriented amorphous phase. A high degree of crystallinity and a low amorphous orientation coefficient tend to result in a low heat shrinkage rate. Thus, the polyglycolic acid fiber of the present embodiment has low heat shrinkage.

[0038] In addition, the polyglycolic acid fiber of this embodiment has a low amorphous orientation coefficient. Hydrolysis of polyglycolic acid is initiated by the diffusion of water into the amorphous part. Sekine et al. ((1) Sekine, S., Akieda, H., Ando, ​​I., Asakura, T. A Study of the Relationship between the Tensile Strength and Dynamics of As-spun and Drawn Poly(glycolic acid) Fibers. Polym. J.40, 10-16 (2008). (2) Sekine, S., Yamauchi, K., Aoki, A., Asakura, T. Heterogeneous structure of Poly(glycolic acid) fiber studied with differential scanning calorimeter, X-ray diffraction, solid-state NMR and molecular dynamic simulation. Polymer 50, 6083-6090 (2009).) have shown that the presence of highly oriented amorphous parts suppresses hydrolysis. In other words, assuming that the diffusion rate of water into the amorphous portion is affected by the orientation of the amorphous portion, the polyglycolic acid fiber of this embodiment, which has a low amorphous orientation coefficient, has a microscopic structure that allows water to easily penetrate, and therefore the polyglycolic acid fiber of this embodiment has high hydrolysis resistance.

[0039] In addition, the polyglycolic acid fiber of the present embodiment may have two or more melting peaks in DSC. This is believed to be because when a developed crystalline phase is formed in the polyglycolic acid fiber, the crystalline phase is less likely to melt than the other parts, resulting in a sufficient difference in melting point. Therefore, such polyglycolic acid fibers having two or more melting peaks tend to have lower heat shrinkage.

[0040] The polyglycolic acid fiber of this embodiment may have a fiber diameter of 5 to 40 μm. In this fiber diameter range, the polyglycolic acid fiber of this embodiment may be produced so as to have both a good fiber morphology and the above-mentioned good microscopic structure characteristics. Thus, the polyglycolic acid fiber having this fiber diameter has good productivity and can suppress the occurrence of poor appearance such as curling.

[0041] The polyglycolic acid fiber of this embodiment can be produced by the production method described below.

[0042] [Method of manufacturing polyglycolic acid fiber] A method for producing polyglycolic acid fibers according to one embodiment of the present invention comprises a first step of discharging polyglycolic acid molten at a melting temperature T°C in an extruder from a spinneret, and a second step of obtaining polyglycolic acid fibers by recovering the fibrous molten polyglycolic acid discharged from the spinneret into a gas phase at a spinning speed Vm / min, and satisfies the following conditions (i) to (iii): (i) 250≦T≦300 (ii) V≧3000 (iii) V / T ≧ 11.5

[0043] The first and second steps in the production method of this embodiment can be carried out by a known method also known as a high-speed melt spinning method, so long as the above conditions are satisfied.

[0044] [First step] The melting temperature (T°C) in the first step is 250°C or more and 300°C or less. The melting temperature of 250 to 300°C allows a good melt of polyglycolic acid to be discharged from the spinneret. If the melting temperature is too low, the melting of polyglycolic acid may be insufficient. This may make it difficult to discharge the melt of polyglycolic acid from the spinneret, and the load on the extruder may increase, causing the screw of the extruder to stop. If the melting temperature is too high, polyglycolic acid may be thermally decomposed, and the decrease in the molecular weight of polyglycolic acid due to the thermal decomposition may be promoted.

[0045] The melting temperature in the first step is preferably 255° C. or higher, more preferably 260° C. or higher, from the viewpoint of sufficiently dissolving the polyglycolic acid, and is preferably 295° C. or lower, more preferably 290° C. or lower, from the viewpoint of suppressing thermal decomposition of the polyglycolic acid.

[0046] In the first step, a melt of polyglycolic acid is discharged from a spinneret connected to an extruder.

[0047] In this embodiment, the spinneret may be of a type known in the art, depending on the application of the resulting polyglycolic acid fiber. The shape of the outlet hole of the spinneret may be determined as appropriate. Examples of the shape of the outlet hole of the spinneret include a circle, a square, a triangle, a star, etc. The diameter of the outlet hole of the spinneret may be determined as appropriate. The number of outlet holes of the spinneret may be determined as appropriate depending on the production conditions, and may be one or more.

[0048] The first step can be carried out by a known extrusion molding machine. From the viewpoint of stably discharging the melt of polyglycolic acid from the spinneret, it is preferable to send the melt of polyglycolic acid toward the spinneret using a quantitative fluid supplying device such as a gear pump.

[0049] In the first step, the discharge rate of the molten polyglycolic acid from the spinneret may be appropriately determined depending on the fiber diameter of the polyglycolic acid fiber to be produced and the spinning speed described below. In this embodiment, the discharge rate per discharge hole of the spinneret may be appropriately determined within the range of, for example, 0.1 to 13.7 g / min.

[0050] [Second step] In the second step, the spinning speed (Vm / min) is the speed at which the molten material discharged from the spinneret into the gas phase is cooled and solidified to be recovered as fibrous polyglycolic acid. The fiber can be recovered by winding it up on a winder. The spinning speed is represented by the length of the spinning per unit time at the time of recovery, and in the case of recovery by winding up on a winder, it is represented by the length of the fiber wound up on the winder per unit time.

[0051] The spinning speed in the second step is 3000 m / min or more. When the spinning speed is 3000 m / min or more, it is possible to mold the molten polyglycolic acid discharged from the spinneret into an appropriate fiber shape, and at the same time, the molecular structure of polyglycolic acid in the polyglycolic acid fiber is made into a desired state. In this way, the recovery of the molten material in the second step forms the outer shape of the fiber and at the same time builds the microscopic internal structure of the fiber. The desired state of the molecular structure is a state in which the molecular chains of polyglycolic acid are crystallized while being oriented in the elongation direction. In this embodiment, the construction of such a desired internal structure is also called "oriented crystallization".

[0052] If the spinning speed is too low, the orientation of the molecular chains of the polyglycolic acid fiber may be insufficient and may not lead to crystallization, whereas if the spinning speed is too high, thread breakage may occur. From the viewpoint of achieving oriented crystallization, the spinning speed is preferably 4000 m / min or more. Moreover, from the viewpoint of suppressing the occurrence of thread breakage, the spinning speed is preferably 10000 m / min or less, more preferably 9000 m / min or less, and even more preferably 8000 m / min or less.

[0053] In the second step, the molten polyglycolic acid discharged from the spinneret is formed into a fiber, stretched, and cooled during recovery. The length from the discharge hole of the spinneret to the recovery position is called the spin line, and the length of the spin line can be appropriately determined within a range in which a desired microscopic internal structure is constructed.

[0054] In the production method of this embodiment, the ratio of the spinning speed (V) to the melting temperature (T) (V / T (m / (min·°C))) is 11.5 or more. If this ratio is too small, the above-mentioned oriented crystallization becomes insufficient, and the crystallization degree of the polyglycolic acid in the recovered polyglycolic acid fiber may be low, or the birefringence may be low. From the viewpoint of producing polyglycolic acid fiber with sufficient oriented crystallization, the above ratio is preferably 12.0 m / (min·°C) or more, and may be 40.0 m / (min·°C) or less.

[0055] [Other processes] The manufacturing method of this embodiment may further include steps other than the first step and the second step described above, as long as the effects of this embodiment can be obtained.

[0056] For example, the manufacturing method of this embodiment may further include a step of feeding a material containing polyglycolic acid into an extruder prior to the first step. The form of the material may be any form known in the extrusion molding of resins, and examples thereof include pellets, powder, granules, flakes, and chunks. The material may be fed into the extruder all at once, or may be fed in multiple batches, or may be fed from multiple points of the extruder simultaneously or sequentially.

[0057] The manufacturing method of this embodiment may further include a step of cooling the melt of fibrous polyglycolic acid on the spinning line in the second step. In the second step, the melt of fibrous polyglycolic acid moves in the gas phase and is air-cooled during the process. The cooling step may be a step of supplying cold air to the fibrous melt, or a step of supplying hot air. The cooling step may be a step of appropriately adjusting the length from the discharge hole of the spinneret to the position where the polyglycolic acid fiber is collected, or a step of appropriately adjusting the cooling time depending on the spinning speed.

[0058] The manufacturing method of this embodiment may further include a step of adjusting the temperature of the molten material discharged from the spinneret in the second step. Such a temperature adjustment step can be performed by a heating cylinder disposed immediately below the spinneret and surrounding the discharge port. The temperature adjustment step may be a step of maintaining the temperature of the space inside the heating cylinder at 80 to 320°C.

[0059] Furthermore, the manufacturing method of this embodiment does not include a stretching step of the polyglycolic acid fiber recovered in the second step. The stretching step referred to here is a step of stretching the polyglycolic acid fiber already formed into a fiber shape to change the internal structure, such as the molecular structure and crystal structure, of the polyglycolic acid fiber, and construct an internal structure that expresses the physical properties of the fiber. In this embodiment, the above-mentioned first and second steps produce polyglycolic acid fibers that are formed into a fiber shape and have an internal structure that expresses the desired physical properties of the fiber, so the above-mentioned stretching step is not necessary. This is because performing the above-mentioned stretching step on polyglycolic acid fibers that already have an internal structure that expresses the desired physical properties may change the above-mentioned internal structure of the polyglycolic acid fiber into an internal structure that cannot express the desired physical properties.

[0060] [Manufacturing equipment] The manufacturing method of this embodiment can be carried out by the high-speed melt spinning method as described above, and can be carried out using a known apparatus capable of carrying out the method. Fig. 1 is a schematic diagram showing an example of the configuration of a high-speed melt spinning apparatus capable of producing the polyglycolic acid fiber according to one embodiment of the present invention.

[0061] As shown in Fig. 1, the high-speed melt spinning apparatus 1 has an extruder 11 having a cylinder in which a screw is housed, a hopper 12 for feeding a fiber material into the cylinder, a gear pump 13 for feeding the melt in the cylinder, a conduit 14 which is a flow path for the melt fed by the gear pump 13, a spinneret 15 for discharging the melt that has passed through the conduit 14 to the outside, and a winder 16 for winding up the melt F of fibrous polyglycolic acid discharged from the spinneret 15 at high speed. The extruder 11 is a device capable of producing a melt of polyglycolic acid at the melting temperature described above, and the winder 16 is a device capable of winding up the melt F while stretching it at the spinning speed described above. The distance from the spinneret 15 to the winder 16 can be appropriately adjusted, for example, within a range of 1 to 5 m.

[0062] [Action and Effect] In the manufacturing method of this embodiment, a melt of polyglycolic acid melted at a specific melting temperature T° C. is discharged from a spinneret, and the discharged melt of fibrous polyglycolic acid is stretched in a gas phase at a specific spinning speed and collected by a winder. The melting temperature and the spinning speed are set to a specific ratio of the spinning speed to the melting temperature.

[0063] In the manufacturing method of this embodiment, a melt of polyglycolic acid at a sufficiently high temperature is discharged from a spinneret, and the discharged melt is elongated by subsequent recovery and recovered by winding or the like. The melt becomes a polyglycolic acid fiber in which an internal structure exhibiting desired physical properties is constructed before this recovery. In this way, the manufacturing method of this embodiment forms a fiber of polyglycolic acid from the melt of polyglycolic acid, while constructing a desired internal structure inside the fiber. The fibrous melt is oriented and crystallized by elongation due to recovery. The ratio of the spinning speed to the melting temperature can be said to be one parameter for achieving appropriate oriented crystallization. According to the manufacturing method of this embodiment, it is possible to manufacture a polyglycolic acid fiber having a low heat shrinkage rate (at 100°C) and high hydrolysis property. For example, the manufacturing method of this embodiment can manufacture the polyglycolic acid fiber of this embodiment having the above-mentioned characteristics (A) to (C).

[0064] The manufacturing method of this embodiment is carried out as described above, based on the discovery that polyglycolic acid fibers having the above-mentioned characteristic internal structure can be obtained by applying polyglycolic acid to a high-speed melt spinning method.

[0065] In the manufacturing method of this embodiment, in order to realize oriented crystallization, it is considered effective to pull up the melt of fibrous polyglycolic acid at a high speed while the melt is cooled to a certain degree.

[0066] By controlling the elongation process of the melt in the spinning line, it becomes easier to construct an internal structure that allows the polyglycolic acid fiber to exhibit desired physical properties. In other words, by adjusting the spinning speed or melting temperature in the spinning line, a large elongation stress is applied to the melt in the spinning line, thereby realizing oriented crystallization. The increase in elongation stress is caused by an increase in tension based on inertial force or air resistance and an increase in the force resisting deformation caused by the magnitude of the elongation strain rate. The elongation profile of the melt in such a spinning line can be appropriately set by adjusting the above-mentioned features (i) to (iii), or by adopting the above-mentioned cooling process, or by adopting the above-mentioned heating barrel. The "elongation profile of the melt in the spinning line" means the transition of the elongation stress of the fibrous material at each point from the discharge port to the winding.

[0067] For example, when the melting temperature of the fibrous polyglycolic acid is low, the melt is recovered at a high speed, so that a sufficiently strong stress can be generated in the fibrous polyglycolic acid, which may be preferable from the viewpoint of sufficiently advancing the oriented crystallization. Also, when the melting temperature is high, the solidification point (position) shifts to the winding side, but by further increasing the spinning speed, it becomes possible to generate a sufficient stress in the fibrous polyglycolic acid.

[0068] The position and strength of the stress generated in the fibrous polyglycolic acid during collection on the spin line can be identified or estimated based on experimentally measured values ​​or on calculated values ​​obtained by computer simulation. The production of polyglycolic acid fibers that generates such stress in the fibrous polyglycolic acid can be appropriately realized by adjusting the configuration of the production apparatus or the operating conditions thereof.

[0069] Therefore, in the process of recovering fibrous polyglycolic acid, it is expected that optimization according to the production conditions of polyglycolic acid fibers can be achieved by adjusting the elongation profile on the spinning line so that the desired elongation stress is generated in the fibrous polyglycolic acid at the desired position on the spinning line.

[0070] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in the different embodiments are also included in the technical scope of the present invention.

[0071] 〔summary〕 As is clear from the above description, the polyglycolic acid fiber according to the embodiment of the present invention has (A) a crystallinity of 20% or more, (B) a birefringence of 35×10 -3 and (C) the amorphous orientation coefficient is 0.30 or less. The method for producing polyglycolic acid fiber in this embodiment includes a step of discharging polyglycolic acid melted at a melting temperature T°C in an extruder from a spinneret, and a step of obtaining polyglycolic acid fiber by recovering the fibrous polyglycolic acid melt discharged from the spinneret into a gas phase at a spinning speed Vm / min, and satisfies the conditions of (i) 250≦T≦300, (ii) V≧3000, and (iii) V / T≧11.5. Thus, according to the embodiment of the present invention, it is possible to provide polyglycolic acid fiber having low heat shrinkability and easy hydrolysis.

[0072] The polyglycolic acid fiber of an embodiment of the present invention has a molecular weight retention rate of 50% or less after immersion in a phosphate buffer solution at 37°C for two weeks, which is even more effective from the standpoint of not only being easily hydrolyzable but also suppressing the occurrence of inflammation when applied to a living body.

[0073] Furthermore, it is even more effective from the viewpoint of reducing heat shrinkage that the polyglycolic acid fiber of an embodiment of the present invention has two or more melting peaks at 220° C. or higher as detected by differential scanning calorimetry.

[0074] Furthermore, it is even more effective for the polyglycolic acid fiber of the embodiment of the present invention to have a fiber diameter of 5 μm or more and 40 μm or less in terms of improving the productivity of the polyglycolic acid fiber and suppressing the occurrence of defects in appearance.

[0075] In the method for producing polyglycolic acid fibers in an embodiment of the present invention, the produced polyglycolic acid fibers may have the above-mentioned properties (A) to (C). The method is suitable for producing the polyglycolic acid fibers of this embodiment. EXAMPLES

[0076] Example 1 Using a high-speed melt spinning apparatus as shown in FIG. 1, polyglycolic acid fiber 1 was produced under the following conditions. <Condition> Material: Polyglycolic acid (melting point 220°C, melt viscosity 960 Pa·s (temperature 270°C, shear rate 122 s -1 )) Melting temperature (T): 270℃ Spinneret: 1 hole (nozzle hole diameter 1.0 mm) Discharge rate (per hole): 5.0g / min Spinning speed (V): 4000m / min

[0077] Example 2 Polyglycolic acid fiber 2 was obtained in the same manner as in Example 1, except that the spinning speed was changed to 5000 m / min.

[0078] Example 3 Polyglycolic acid fiber 3 was obtained in the same manner as in Example 1, except that the spinning speed was changed to 6000 m / min.

[0079] Example 4 Polyglycolic acid fiber 4 was obtained in the same manner as in Example 1, except that the spinning speed was changed to 7000 m / min.

[0080] Example 5 Polyglycolic Acid Fiber 5 was obtained in the same manner as in Example 1, except that the melting temperature of polyglycolic acid was changed to 255° C. and the spinning speed was changed to 3000 m / min.

[0081] Example 6 Polyglycolic acid fiber 6 was obtained in the same manner as in Example 5, except that the spinning speed was changed to 4000 m / min.

[0082] Example 7 Polyglycolic acid fiber 7 was obtained in the same manner as in Example 5, except that the spinning speed was changed to 5000 m / min.

[0083] Comparative Example 1 Polyglycolic acid fiber C1 was obtained in the same manner as in Example 1, except that the spinning speed was changed to 1000 m / min.

[0084] Comparative Example 2 Polyglycolic acid fiber C2 was obtained in the same manner as in Example 1, except that the spinning speed was changed to 3000 m / min.

[0085] Comparative Example 3 Polyglycolic acid fiber C3 was obtained in the same manner as in Example 5, except that the spinning speed was changed to 2000 m / min.

[0086] Comparative Example 4 Polyglycolic acid fibers were produced using a direct spinning and drawing apparatus 2 as shown in Fig. 2. Fig. 2 is a schematic diagram showing an example of the configuration of a direct spinning and drawing apparatus used for producing polyglycolic acid fibers of a comparative example.

[0087] 2, the direct spinning and drawing apparatus 2 has a spinneret 17 having multiple discharge ports instead of the spinneret 15, and has a first godet roll 19 instead of the winder 16, which receives the fiber F1 produced by spinning and sends it out to a drawing device in a subsequent stage. The direct spinning and drawing apparatus 2 further has a drawing device, and further has a heating cylinder 18 directly below the spinneret 17. Except for these, the direct spinning and drawing apparatus 2 has the same configuration as the high-speed melt spinning apparatus 1 described above.

[0088] The drawing device has a second godet roll 21, a third godet roll 22, and a fourth godet roll 23 for drawing the fiber F1, and a winder (also called a "winder") 24 for winding up the drawn fiber F2.

[0089] Polyglycolic acid fiber C4 was produced under the following conditions using a direct spinning and drawing apparatus as shown in Fig. 2. In order to maintain the tension of fiber F2, the rotation speed of the second godet roll 21 was set about 1% higher than the rotation speed of the first godet roll 19. <Condition> Material: Polyglycolic acid (melting point 220°C, melt viscosity 960 Pa·s (temperature 270°C, shear rate 122 s -1 )) Melting temperature: 255℃ Spinneret: 24 holes (nozzle hole diameter 0.25 mm) Discharge rate (per hole): 0.292g / min Heating cylinder: Length 20cm, temperature 120℃ Spinning speed: 150 m / min Spinning temperature (temperature of first godet roll 19): 25°C Stretching ratio: 5.0 times (between the second godet roll 21 and the third godet roll 22) Stretching temperature (temperature of second godet roll 21): 65°C Relaxation and heat treatment temperature (temperature of the third godet roll 22 and the fourth godet roll 23): 90°C

[0090] Comparative Example 5 Polyglycolic acid fiber C5 was obtained in the same manner as in Comparative Example 4, except that the draw ratio was changed to 4.0 times.

[0091] Comparative Example 6 Polyglycolic acid fiber C6 was obtained in the same manner as in Comparative Example 4, except that the draw ratio was changed to 3.0 times.

[0092] 〔evaluation〕 [Fiber diameter] The diameter of each of the polyglycolic acid fibers 1 to 7 and C1 to C6 was measured using a polarizing microscope ("BX53-P", manufactured by Olympus Corporation). The average value of the diameters measured for five samples of each polyglycolic acid fiber was regarded as the fiber diameter of the fiber.

[0093] [Crystallization degree] The density ρ of each of the polyglycolic acid fibers 1 to 7 and C1 to C6 was measured using a density gradient tube prepared from 1,2-dichloroethane and carbon tetrachloride, after immersing the sample in the density gradient tube at 25°C for 24 hours. c is the measured density ρ (g / cm 3 ) was calculated using the following formula (1). In formula (1), ρ c and ρ a respectively represent the crystalline density and the amorphous density of polyglycolic acid, and in this example, c =1.69g / cm 3 , ρ a =1.50g / cm 3 It was decided.

[0094]

number

[0095] [Birefringence] The birefringence of each of the polyglycolic acid fibers 1 to 7 and C1 to C6 was measured using a polarizing microscope equipped with a Bereck compensator ("BX53-P", manufactured by Olympus Corporation). The average value of the birefringence measured for the five samples of each polyglycolic acid fiber was regarded as the birefringence of the fiber.

[0096] [Crystal orientation coefficient] Since the diffraction of the (00l) plane was not obtained and the orientation of the c-axis could not be directly evaluated, the crystal orientation coefficient f c was calculated from the following formula (2) according to the calculation method of Wilchinsky. <cos 2 φ c represents the orientation coefficient of the c-axis, and was calculated by the following formula (3). In formula (3), <cos 2 φ1> and <cos 2φ2> represents the cosine of the mean square orientation angle calculated from the diffraction intensity curves of the (110) plane and the (020) plane, respectively, and was calculated by the following formula (4). In the above formula (3), θ1 and θ2 represent the angles that the (110) plane and the (020) plane make with the b-axis, respectively, and in this example, θ1 and θ2 were set to θ1=49.9° and θ2=0°, respectively, based on the crystal structure of polyglycolic acid.

[0097]

number

[0098] In the above formula (4), N(φ) represents the diffraction intensity curve. The diffraction intensity curves were obtained by obtaining wide-angle X-ray diffraction (WAND) images of polyglycolic acid fibers 1 to 7 and C4 to C6 using an X-ray diffractometer (NANO-Viewer, manufactured by Rigaku Corporation). In this case, nickel-filtered CuKα rays (wavelength 0.154 nm) generated at 40 kV and 20 mA were irradiated perpendicularly to the sample for 30 minutes, and wide-angle X-ray diffraction images were obtained using an imaging plate.

[0099] The diffraction intensity curve was corrected for air scattering. The (110) plane contains an amorphous halo and the (101) plane, so it was isolated by fitting with the Gaussian function of the following formula (5). The (020) plane also has a diffraction angle close to that of the (102) plane, so it was isolated using a similar method. In formula (5), N is the peak intensity of the diffraction intensity, φ0 is the position of the peak intensity, and w is the half-width.

[0100]

number

[0101] For the polyglycolic acid fibers C1 to C3, no diffraction images were obtained, and the crystal orientation coefficient f c It was not possible to calculate

[0102] [Amorphous orientation coefficient] The birefringence Δn is expressed by the following formula (6) assuming a two-phase model of crystal and amorphous. In the following formula (6), the contribution of the form birefringence to the total birefringence is assumed to be small and is ignored. Here, X c is the crystallinity, f c is the crystal orientation coefficient, f a is the amorphous orientation coefficient, Δn c and Δn a are the intrinsic birefringences of crystalline and amorphous polyglycolic acid, respectively.

[0103]

number

[0104] In the above formula (6), Δn c and Δn a are calculated using the atomic bond polarizabilities of Bunn et al., and Δn c = 0.137, Δn a =0.117.

[0105] For the polyglycolic acid fibers C1 to C3, the crystal orientation coefficient f c Since it was not possible to calculate the amorphous orientation coefficient f a was not calculated.

[0106] [Melting point] The melting peaks of each of the polyglycolic acid fibers 1 to 7 and C1 to C6 were measured using a differential scanning calorimeter (DSC) (DSC-60 A plus, manufactured by Shimadzu Corporation). Approximately 10 mg of the sample was weighed out and sealed in an aluminum pan. The sample was heated from 0°C to 280°C at a rate of 10°C / min under a nitrogen atmosphere (flow rate 10 mL / min). The measured melting peak was taken as the melting point of the fiber.

[0107] [Heat shrinkage rate] The heat shrinkage of each of the polyglycolic acid fibers 1 to 7 and C1 to C6 was measured. A sample of 100 m was wound on a winding machine with a frame circumference of 1 m, one end of the obtained skein was fixed, and a 20 g weight was hung on the other end to measure the skein length L. Next, the weight was removed, and the skein was hung in a dry heat oven at 100°C and left for 30 minutes, and then cooled to room temperature. Then, one end of the skein was fixed again, and a 20 g weight was hung on the other end to measure the skein length LHT, and the heat shrinkage (%) was calculated by the following formula (7). Here, L is the skein length (m) before heat treatment, and LHT is the skein length (m) after heat treatment. If the heat shrinkage is 5% or less, it can be determined that there is no practical problem in the use of fiber materials. (formula) Heat shrinkage rate (%) = (L-LHT) / L x 100 (7)

[0108] [Molecular weight retention rate] The hydrolysis characteristics of each of the polyglycolic acid fibers 1 to 7 and C1 to C6 were evaluated. The weight average molecular weight of each polyglycolic acid fiber was measured. Next, each polyglycolic acid fiber was immersed in a phosphate buffer solution and left to stand in an oven set at 37°C for two weeks, and each polyglycolic acid fiber was taken out and the weight average molecular weight of each polyglycolic acid fiber was measured by gel permeation chromatography (GPC). The percentage of the weight average molecular weight of the polyglycolic acid fiber before the above immersion and standing to the weight average molecular weight of the polyglycolic acid fiber after the above immersion and standing was calculated as the molecular weight retention rate, and the hydrolysis characteristics were evaluated based on the molecular weight retention rate. If the molecular weight retention rate is 50% or less, it can be determined that there is no practical problem in applications utilizing the easy hydrolysis property.

[0109] The weight average molecular weight of each polyglycolic acid fiber was measured as follows. 10 mg of polyglycolic acid fiber was weighed and dissolved in 0.5 mL of dimethyl sulfoxide at 150° C. The solution was cooled to room temperature, dissolved in 10 mL of hexafluoro-2-propanol containing 5 mM sodium trifluoroacetate, and filtered through a 0.2 μm membrane filter. This solution was poured into a GPC apparatus ("Shodex-104", Showa Denko K.K.), and the weight average molecular weight of the polyglycolic acid fiber was determined as a polymethyl methacrylate equivalent value.

[0110] Table 1 shows the production conditions and the above-mentioned evaluation results for each of the polyglycolic acid fibers 1 to 7 and C1 to C6.

[0111] [Table 1]

[0112] [Consideration] As is clear from Table 1, all of the polyglycolic acid fibers 1 to 7 have sufficiently low heat shrinkage and sufficiently good hydrolysis properties. This is believed to be because the molten fibrous polyglycolic acid is wound and stretched at a sufficiently high speed during spinning, generating an appropriate amount of stress in the molten material, which induces orientation and crystallization of the polyglycolic acid in the fiber as the fiber is formed.

[0113] In each of the polyglycolic acid fibers 1 to 7, the degree of crystallinity is relatively high and the crystalline phase exhibits high orientation, whereas the orientation of the amorphous phase is low. Thus, it is considered that the polyglycolic acid fibers 1 to 7 have low heat shrinkage because of the sufficiently high degree of crystallinity and sufficiently low amorphous orientation coefficient.

[0114] In addition, since the orientation in the amorphous phase within the polyglycolic acid fibers is low, water easily penetrates and diffuses within the fibers of the polyglycolic acid fibers 1 to 7, making them more susceptible to hydrolysis, and it is believed that this results in sufficiently high ease of hydrolysis.

[0115] Moreover, polyglycolic acid fibers 2-4 and 7 have two melting points, about 220-250°C and about 230-245°C, and have a relatively high degree of crystallinity. The former melting point in polyglycolic acid fibers 2-4 and 7 is considered to be the melting point of polyglycolic acid, and the latter melting point is considered to be the melting point of a component that is less meltable than polyglycolic acid, that is, the melting point derived from the developed crystals of polyglycolic acid. In polyglycolic acid fibers 2-4 and 7, the crystallization is more advanced in the above-mentioned oriented crystallization, and therefore it is considered that the lower heat shrinkage is exhibited. From the above, although it cannot be said in general, it is considered that the low heat shrinkage is contributed by both the low orientation in the amorphous phase and the developed crystal structure of polyglycolic acid.

[0116] On the other hand, polyglycolic acid fibers C1 to C3 have a high moisture content but a high heat shrinkage, which is insufficient in terms of low heat shrinkage. Polyglycolic acid fibers C1 and C3 both have a slow spinning speed and a low V / T. Polyglycolic acid fiber C2 has a low V / T. Furthermore, these fibers have a very low degree of crystallinity, and since no diffraction images were obtained by X-ray irradiation, the crystal orientation coefficients were not obtained. Therefore, polyglycolic acid fibers C1 to C3 are considered to be amorphous fibers.

[0117] Moreover, polyglycolic acid fibers C4 to C6 have higher heat shrinkage and a slower hydrolysis rate than polyglycolic acid fibers 1 to 7. The spinning speed and V / T of polyglycolic acid fibers C4 to C6 are significantly lower, and the manufacturing process includes a drawing step. For this reason, it is considered that the crystal structure develops due to oriented crystallization caused by drawing, and the orientation in the amorphous phase also becomes high, resulting in higher heat shrinkage and a suppressed water diffusion rate, resulting in insufficient hydrolysis. [Industrial Applicability]

[0118] The present invention can be utilized in fiber or fabric materials that require low heat shrinkage and high hydrolysis resistance, such as medical materials including bioabsorbable sutures, and products containing the same. [Explanation of symbols]

[0119] 1. High-speed melt spinning equipment 2. Direct spinning and drawing equipment 11 Extrusion Machine 12 Hopper 13 Gear Pump 14 Conduit 15, 17 Spinneret 16, 25 Winding machine 18 Heating tube 19 First Godet Roll 21 Second Godet Roll 22 Third Godet Roll 23 Fourth Godet Roll 24 Winder

Claims

1. The following characteristics: (A) the crystallinity is 20% or more and 50% or less; (B) Birefringence is 35 x 10 -3 is equal to or greater than 80×10 −3 , and (C) the amorphous orientation coefficient is 0.30 or less; Polyglycolic acid fiber having the structure

2. 2. The polyglycolic acid fiber according to claim 1, which has a molecular weight retention of 50% or less after immersion in a phosphate buffer solution at 37° C. for two weeks.

3. 3. The polyglycolic acid fiber according to claim 1, which has two or more melting peaks at 220° C. or higher as detected by differential scanning calorimetry.

4. 4. The polyglycolic acid fiber according to claim 1, having a fiber diameter of 5 μm or more and 40 μm or less.

5. A step of discharging polyglycolic acid molten at a melting temperature T°C from a spinneret in an extruder; and recovering the molten fibrous polyglycolic acid extruded from the spinneret into the gas phase at a spinning speed of Vm / min to obtain polyglycolic acid fibers, the process comprising the steps of: (i) 250≦T≦300 (ii) V≧3000 (iii) V / T≧11.5 A method for producing polyglycolic acid fibers that satisfies the above requirements.

6. The polyglycolic acid fiber has the following characteristics: (B) the birefringence is 35×10 −3 or more and 80×10 −3 or less; The method for producing polyglycolic acid fibers according to claim 5 , comprising the steps of:

7. The polyglycolic acid fiber has the following characteristics: (A) the crystallinity is 20% or more and 50% or less; (B) Birefringence is 35 x 10 -3 is equal to or greater than 80×10 −3 , and (C) the amorphous orientation coefficient is 0.30 or less; The method for producing polyglycolic acid fibers according to claim 5 , comprising the steps of:

Citation Information

Patent Citations

  • Method for producing fiber for high-tenacity bioabsorbable suture and the fiber for the suture

    JP2004250853A

  • Biodegradable aliphatic polyester drawn yarn and method for producing the same

    JP2012251277A

  • Aliphatic polyester resin molding and method for producing the same

    JP2017155094A

  • Method for producing polyglycolic acid fiber

    WO2010143526A1

  • Polyglycolic acid fibers and method for producing same

    WO2011016321A1